1988
DOI: 10.1515/botm.1988.31.4.307
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Induced Changes in Peroxidase Activity in the Green Seaweed Ulva lactuca

Abstract: Fronds of Ulva lactuca were cultured in seawater of different salinity levels for 20 days under laboratory conditions, and their cytoplasmic peroxidase activities determined. The activity was maximal in normal seawater (100%) but it significantly decreased at hypo-and hypertonic concentrations. The decrease in the activity was gradual under hypersaline conditions. However, a steep fall resulted when the concentration decreased from normal to hyposaline. Increase in the frond length revealed a similar pattern. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The percentages of recovery rates of chlorophyll of Nori and Sea Lettuce are similar to the observed values in peas (60-87%, Gallardo-Guerrero, Gandul-Rojas, & Mínguez-Mosquera, 2008) and in an oily mixture of chlorophyll standards (50-82%, Gandul-Rojas, Gallardo-Guerrero, & Mínguez-Mosquera, 2009). The loss of chlorophyll pigments during in vitro digestion may be due to the activity of peroxidase and lipoxygenase, which contributes to degrading chlorophyll pigments, as stated previously (Gallardo-Guerrero, Gandul-Rojas, & Mínguez-Mosquera, 2008) since peroxidase (Murthy, Sharma, & Rao, 1988) and lipoxygenase (Kuo, Hwang, Hsu, & Pan, 1996) has been identified to be widely distributed in seaweed.…”
Section: Recovery Rate Of Chlorophyll Derivatives From Fresh Dried Sesupporting
confidence: 85%
“…The percentages of recovery rates of chlorophyll of Nori and Sea Lettuce are similar to the observed values in peas (60-87%, Gallardo-Guerrero, Gandul-Rojas, & Mínguez-Mosquera, 2008) and in an oily mixture of chlorophyll standards (50-82%, Gandul-Rojas, Gallardo-Guerrero, & Mínguez-Mosquera, 2009). The loss of chlorophyll pigments during in vitro digestion may be due to the activity of peroxidase and lipoxygenase, which contributes to degrading chlorophyll pigments, as stated previously (Gallardo-Guerrero, Gandul-Rojas, & Mínguez-Mosquera, 2008) since peroxidase (Murthy, Sharma, & Rao, 1988) and lipoxygenase (Kuo, Hwang, Hsu, & Pan, 1996) has been identified to be widely distributed in seaweed.…”
Section: Recovery Rate Of Chlorophyll Derivatives From Fresh Dried Sesupporting
confidence: 85%
“…Similarly, Kamer and Fong (2000) found that exposure to 15 psu conditions for 5 d periods decreased E. intestinalis growth. Ulva lactuca growth has been reduced by salinity between 20 and 30 psu (Murthy et al 1988, Friedlander 1992, and other less closely related bloom-forming species (Gracilaria spp., Cladophora spp.) have also been negatively affected by reduced salinity (Bird & McLachlan 1986, Thomas et al 1988.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain osmotic balance with the external environment, algae regulate their internal solute concentration, which requires energy (Kirst 1989). As a result, algal growth and productivity may be reduced (Bird et al 1979, Bird & McLachlan 1986, Edwards et al 1988, Murthy et al 1988, Thomas et al 1988, Karsten & Kirst 1989, Friedlander 1992.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that other green macroalgae, e.g., Enteromorpha, are more tolerant of reduced or elevated salinity than Ulva (Martins et al 1999). In contrast, U. lactuca in culture was more tolerant of hyper-than hyposalinity (Murthy et al 1988). U. rotundata in the field has been growing in salinities ranging from 26 to36 psu (De Casabianca 1989), and U. rigida bloomed in summer when salinity remained above 20 psu (Fillit 1995).…”
Section: Growth Rate and Nutrient Uptakementioning
confidence: 99%